Detection of S-100 labelled cells in nasopharyngeal carcinoma. - Lauriola, L (1984)
S-100 antigen containing cells with dendritic features, recognisable by morphological and immunohistochemical criteria as belonging to the Langerhans' or interdigitating reticulum cell type, have been found in undifferentiated nasopharyngeal carcinoma. The presence of these cells, which have a special function of antigen presentation in immune responses, may be involved in a possible modulation of nasopharyngeal carcinoma associated Epstein-Barr virus infection and host-tumour interactions.